2011
DOI: 10.1002/pbc.23058
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Burkitt lymphoma of maxillofacial region: results of induction treatment with cyclophosphamide plus methotrexate in West Africa

Abstract: Background Burkitt lymphoma is frequent a cancer in the developing countries where its treatment is based on non‐intensive chemotherapy protocols. The purpose of this study was to assess the effectiveness and the toxicity of a non–intensive chemotherapy protocol combining cyclophosphamide and methotrexate in children with Burkitt lymphoma of the maxillofacial region. Procedure A retrospective descriptive study was carried out in patients with Burkitt lymphoma of maxillofacial region who received at least one w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The study conducted in Southern and Eastern Europe showed peak age of 5-9 years, 43 whilst the American study reported 4-7 years peak age in sporadic BL variant with male to female ratio of 2:1.8 44 and similar patterns are seen in African studies. 45 The predominance of women infected by HIV reflects the South Africa national demographics of HIV prevalence 46 and is comparable to other South African 47,48 and international studies. 49 A predominance of presentation in abdominal and pelvic sites rather than in the jaw distinguishes this study of South African patients from those reported from endemic regions in Africa.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The study conducted in Southern and Eastern Europe showed peak age of 5-9 years, 43 whilst the American study reported 4-7 years peak age in sporadic BL variant with male to female ratio of 2:1.8 44 and similar patterns are seen in African studies. 45 The predominance of women infected by HIV reflects the South Africa national demographics of HIV prevalence 46 and is comparable to other South African 47,48 and international studies. 49 A predominance of presentation in abdominal and pelvic sites rather than in the jaw distinguishes this study of South African patients from those reported from endemic regions in Africa.…”
Section: Discussionsupporting
confidence: 72%
“…Our study showed that paediatric group had an outcome comparable to GFAOP study (overall survival: 69% vs 61%), importantly both studies used similar treatment protocol (LMB protocol). 35,45 More than one-third (n = 13) of our adult group were treated with adapted paediatric LMB protocol, four patients achieved a 2-year survival; this was lower than the study of an adapted paediatric LMB protocol which showed an event-free survival rate of 65% at 2 years amongst 72 adults with BL. 19 Hyper-CVAD group (n = 11) showed 36% overall outcome; these findings are in contrast with a similar study conducted by Thomas et al in which hyper-CVAD alone showed 53% OS, whilst hyper-CVAD plus rituximab was reported at 86% OS.…”
Section: Discussionmentioning
confidence: 75%
“…Published data from African collaborative studies are scarce and overall survival rates varied from 5% to 80% . Most reports are from single‐unit treatment centres and the majority reported the outcomes for BL , nephroblastoma , and retinoblastoma . The Franco‐African Childhood Cancer Group (GFAOP) is the first collaborative group in Africa, founded in 2000, with the aim of providing paediatric cancer treatment .…”
Section: Childhood Cancer Treatment In Africamentioning
confidence: 99%
“… 41,51–61 In Sub‐Saharan Africa, where healthcare and social conditions are extremely poor, the therapeutic strategies vary from treatment with cyclophosphamide, alone or in combination, to some cautious attempts with more aggressive schemes (Table IV). 17,22,27,62–81 …”
Section: Epidemiologymentioning
confidence: 99%